Magnesium and Muscle Cramps in End Stage Renal Disease Patients on Chronic Hemodialysis. (9th November 2014) - Lynch, Patrick G.; Abate, Mersema; Suh, Heesuck; Wadhwa, Nand K.
Abstract : We evaluated the frequency and severity of muscle cramps, and the effect of dialysate magnesium on muscle cramps in 62 stable ESRD patients on chronic hemodialysis. Each subject was surveyed twice within a 6-month period. A single nephrology fellow conducted all in-person surveys. During the first survey, the patients were dialyzed with dialysate magnesium of 0.75 meq/L (0.375 mmol/L). Prior to the second survey, the dialysate magnesium was increased to 1.0 meq/L (0.50 mmol/L). The severity of cramps was scored on a 1–10 scale, with 10 indicating maximal severity. The number of patients with muscle cramps was significantly lower with dialysate magnesium of 1.0 meq/L (0.50 mmol/L) (56% versus 77%, P = 0.02 ). No significant difference was observed in interdialytic weight gain, intradialytic ultrafiltration, dry weight, or intradialytic hypotension. The mean ± SD severity score of muscle cramps decreased from 5.34 ± 3.61 to 3.89 ± 3.94 (P = 0 . 003 ). Seven of 31 (23%) patients in the group with low dialysate magnesium while 0/20 (0%) patients receiving high magnesium dialysate terminated hemodialysis early due to cramps (P = 0 . 02 ). Both the number of patients reporting muscle cramps and the severity score decreased with higher dialysate magnesium which contributed to better adherence to hemodialysis treatments.